JUNIOR HIGH SCHOOL STUDENTS' RESPONSES TOWARD THE PROCESS OF TEACHING WRITING NARRATIVE TEXT USING PROJECT-BASED APPROACH - Novi, Novi; Mulyani, Euis Rina; Rhidwan, Silmi Fauziyah (IKIP Siliwangi, 2024)
This study aims to identify students' responses to the use of a project-based approach in teaching writing narrative text. This research was conducted in a junior high school in Cimahi involving 23 students of grade VIII as the research subjects. The method used was qualitative research with a data collection technique through the questionnaire. The data were analyzed both qualitatively using Miles & Huberman (1992) data analysis framework and quantitatively only in sum and percentage. The results showed that the use of a project-based approach was positive toward students' motivation and involvement in the writing learning process. Students feel more motivated and challenged to write because they can work collaboratively in groups and have the opportunity to develop their creative ideas. Meanwhile, students' negative responses to the use of the project-based approach were that they were still confused about the demands and steps to be taken in completing the project. This caused them to feel less confident in completing the project well. The data from the questionnaire shows that using project-based learning in teaching writing provides benefits in learning English writing skills. Therefore, using project-based learning in teaching narrative text writing can improve students' writing ability.